Persepsi Dosen Putri Sekolah Tinggi Ilmu Syariah Hidayatullah Balikpapan Tentang Pelayanan E-Commerce Shopee Perspektif Etika Bisnis Islam - Sitti Ramlah; Istiada Istiada; Maftuha Maftuha (Ulumul Syar'i : Jurnal Ilmu-Ilmu Hukum dan Syariah, 2023)
This research aims to understand the perception of lecturers regarding Shopee's E-commerce services from the perspective of Islamic business ethics. This type of research uses qualitative methods with data collection techniques through interviews. The data collection method involves observation followed by distributing questionnaires. The subjects of this research are lecturers who use Shopee E-commerce. The results of the study show that generally, all lecturers feel that Shopee's E-commerce service is good. However, there are also some situations that cause dissatisfaction among the lecturers. Factors influencing the lecturers' perceptions include service quality, product quality, price, convenience, and emotional factors. From the perspective of Islamic business ethics, lecturers are generally not satisfied. The interviews revealed that Shopee still engages in actions that harm customers, such as ordered items not matching the displayed images, swapped packages, and lack of supervision by Shopee regarding seller honesty.